Social Entrepreneurship Through Mosque Cooperatives in Building Loan-shark-free Society Economy - Muhardi, M; Nurdin, N; Ihwanuddin, Nandang (KnE Social Sciences, 2023)
The existence of mosque cooperatives has driven strong independency both from the economic and social perspectives. The objective of this research is to acknowledge; (a) the social entrepreneurship situation and existence of mosque cooperatives; and (b) the social entrepreneurship concept practiced by mosque cooperatives in building a loan-sharks-free society with economic independence. This research used a descriptive qualitative method with interview, observation, and focus group discussion as data collection instruments. The sample of this research is a number of mosques in Sukabumi Regency that are actively involved in society’s economic development efforts. The analytical tool utilized in this research is SWOT analysis. Based on this research, we concluded that; (a) social entrepreneurship implemented by mosque cooperatives is practiced by providing interests-free capital loans for non-formal economy sectors; and (b) social entrepreneurship implemented by mosque cooperatives is also practiced by taking an active role as a marketer or distribution channel for non-formal sectors. Keywords: economy of society, mosque cooperatives, empowerment